Concrete floor structure and method for manufacturing the same
Patent Information
- Application Number
- JP2025058152
- Authority / Receiving Office
- JP · JP
- Patent Type
- Applications
- Current Assignee / Owner
- Filing Date
- 2025-03-31
- Publication Date
- 2026-10-14
AI Technical Summary
【0010】 本発明によれば、塗り床仕上げ材として、水性硬質ウレタン系塗り床仕上げ材を用いる場合において、セルフレベリング材層に対する塗り床仕上げ材層の付着耐久性を向上させることが可能であり、さらには平滑性に優れるコンクリート床構造体を得ることが可能なコンクリート床構造体の製造方法が提供される。また、本発明によれば、このような製造方法によって得られるコンクリート床構造体が提供される。
Smart Images

Figure 2026165655000001_ABST
Abstract
Description
[Technical Field]
[0001] The present invention relates to a concrete floor structure and a method for manufacturing the same. [Background technology]
[0002] In buildings such as offices, factories, and warehouses, various resin-based floor coatings are commonly used to finish concrete floors. When these floor coatings are used as finishing materials for concrete floors, the abrasion resistance, chemical resistance, and other properties of the floor surface are improved.
[0003] When these floor coatings are applied, known methods for constructing the base layer include, for example, the direct concrete pressing method, the construction joint method using mortars, self-leveling materials, etc. Patent Document 1 discloses a concrete floor structure as a construction joint method, comprising a concrete floor layer and a self-leveling material layer containing a hardened self-leveling material slurry, characterized in that a floor coating layer is formed on the upper surface of the self-leveling material layer of the concrete floor layer by applying a water-based floor coating as a floor coating. [Prior art documents] [Patent Documents]
[0004] [Patent Document 1] Japanese Patent Publication No. 2009-257063 [Overview of the project] [Problems that the invention aims to solve]
[0005] In concrete floor structures, high durability is sometimes required to withstand the long-term use of vehicles that transport heavy objects, such as forklifts and automated guided vehicles (AGVs). In concrete floor structures requiring such high durability, water-based rigid urethane floor coatings are sometimes used as floor finishing materials.
[0006] Incidentally, when the inventors investigated the formation of a floor coating layer on the upper surface of a self-leveling material layer using a water-based rigid urethane floor coating material, they found that because the water-based rigid urethane floor coating material has a large curing shrinkage force, tensile stress is generated due to the warping of the coating film of the floor coating material, and peeling of the floor coating layer from the self-leveling material layer may occur.
[0007] Therefore, the main objective of the present invention is to provide a method for manufacturing a concrete floor structure that, when using a water-based rigid urethane floor coating as the floor coating material, can improve the adhesion durability of the floor coating layer to the self-leveling material layer, and furthermore, can produce a concrete floor structure with excellent smoothness. [Means for solving the problem]
[0008] In an effort to solve the above problems, the inventors of this invention discovered that by incorporating a predetermined amount of resin powder into the self-leveling material layer, the adhesion durability of the floor coating layer to the self-leveling material layer is improved, and a concrete floor structure with excellent smoothness can be obtained, thus completing the present invention.
[0009] The present invention provides a method for manufacturing the concrete floor structure described in [1] and [2], and the concrete floor structure described in [3]. [1] A method for manufacturing a concrete floor structure comprising a concrete floor layer, a self-leveling primer layer, a self-leveling material layer, and a floor coating finish layer in this order, A step of applying a self-leveling primer layer to the upper surface of the concrete floor layer, The process involves applying a self-leveling material slurry containing a self-leveling material with a hydraulic component and resin powder, and water, to the upper surface of the self-leveling material primer layer, and curing the self-leveling material slurry to provide a self-leveling material layer containing the cured product of the self-leveling material slurry. The process involves applying a floor finishing material to the upper surface of the self-leveling material layer and curing the floor finishing material to provide a floor finishing material layer containing the cured product of the floor finishing material, Equipped with, The hydraulic component includes alumina cement, Portland cement, and gypsum. The content of the resin powder is 21.0 parts by mass or more and less than 40.0 parts by mass per 100 parts by mass of the hydraulic component. The aforementioned floor coating material is a water-based rigid urethane floor coating material. A method for manufacturing concrete floor structures. [2] The resin of the resin powder comprises a copolymer having structural units derived from vinyl acetate, A method for manufacturing a concrete floor structure as described in [1]. [3] Concrete floor layer and Self-leveling primer layer, Self-leveling material layer, The floor coating finish layer, They are provided in this order, The self-leveling material layer comprises a self-leveling material containing a hydraulic component and resin powder, and a cured self-leveling material slurry containing water. The hydraulic component includes alumina cement, Portland cement, and gypsum. The content of the resin powder is 21.0 parts by mass or more and less than 40.0 parts by mass per 100 parts by mass of the hydraulic component. The floor coating layer contains hardened material of the floor coating, The aforementioned floor coating material is a water-based rigid urethane floor coating material. Concrete floor structure. [Effects of the Invention]
[0010] According to the present invention, in the case of using a water-based hard urethane-based flooring finishing material as the flooring finishing material, it is possible to improve the adhesion durability of the flooring finishing material layer to the self-leveling material layer, and further, there is provided a method for producing a concrete floor structure capable of obtaining a concrete floor structure excellent in smoothness. Further, according to the present invention, there is provided a concrete floor structure obtained by such a production method. Brief Description of the Drawings
[0011] [Figure 1] Figure 1 is a schematic cross-sectional view showing an embodiment of the method for producing a concrete floor structure, and Figure 1(a), Figure 1(b), Figure 1(c), and Figure 1(d) are process diagrams showing the respective steps. Modes for Carrying Out the Invention
[0012] Hereinafter, embodiments of the present invention will be described with appropriate reference to the drawings. However, the present invention is not limited to the following embodiments.
[0013] In the present specification, a numerical range indicated by using "~" indicates a range including the numerical values stated before and after "~" as the minimum value and the maximum value, respectively. In the numerical ranges described stepwise in the present specification, the upper limit value or the lower limit value described in one numerical range may be replaced with the upper limit value or the lower limit value of another stepwise described numerical range. Further, in the numerical ranges described in the present specification, the upper limit value or the lower limit value of the numerical range may be replaced with the values shown in the Examples. In addition, the individually described upper limit values and lower limit values can be arbitrarily combined.
[0014] In the present specification, the term "process" is not limited to an independent process, and is included in the term as long as the intended action of the process is achieved even when the process cannot be clearly distinguished from other processes.
[0015] The materials exemplified below may be used individually or in combination of two or more, unless otherwise specified. The content of each component in the composition refers to the total amount of any multiple substances present in the composition, unless otherwise specified, if multiple substances corresponding to each component exist in the composition.
[0016] [Manufacturing method for concrete floor structures] Figure 1 is a schematic cross-sectional view showing one embodiment of a method for manufacturing a concrete floor structure, and Figures 1(a), 1(b), 1(c), and 1(d) are process diagrams showing each step. The method for manufacturing the concrete floor structure 20 of this embodiment is a method for manufacturing a concrete floor structure comprising a concrete floor layer 2, a self-leveling material primer layer 4, a self-leveling material layer 6, and a floor coating finish layer 8 in this order, comprising the steps of: providing a self-leveling material primer layer 4 on the upper surface 2A of the concrete floor layer 2 (first step, see Figures 1(a) and 1(b)); and providing a self-leveling material containing a hydraulic component and resin powder and water on the upper surface 4A of the self-leveling material primer layer 4. The process comprises the steps of: pouring a self-leveling material slurry containing and hardening the self-leveling material slurry to provide a self-leveling material layer 6 including the hardened self-leveling material slurry (second step, see Figures 1(b) and 1(c)); and applying a floor coating material to the upper surface 6A of the self-leveling material layer 6 and hardening the floor coating material to provide a floor coating material layer 8 including the hardened floor coating material (third step, see Figures 1(c) and 1(d)).
[0017] <First step> In this process, a self-leveling primer layer 4 is applied to the upper surface 2A of the concrete floor layer 2 (see Figures 1(a) and 1(b)).
[0018] Concrete floor layer 2 forms the floor surface of a typical concrete structure (building, structure). Concrete floor layer 2 may be the concrete floor layer of a building or structure. Concrete floor layer 2 may be formed by mixing cement, fine aggregate, coarse aggregate, superplasticizer, water, etc., in specific proportions and then hardening the mixture. The compressive strength (nominal strength) of the concrete floor layer is 20 N / mm². 2 More than 30N / mm 2 Above, 35N / mm 2 Above or above, or 40 N / mm 2 That's all.
[0019] The self-leveling material primer layer 4 is provided to prevent moisture in the self-leveling material slurry from penetrating into the concrete floor layer 2 when the self-leveling material slurry is poured to form the self-leveling material layer 6 described later, and also to firmly bond the concrete floor layer 2 and the self-leveling material layer 6.
[0020] The self-leveling primer layer 4 can be formed, for example, by applying a self-leveling primer to the concrete floor layer 2 and allowing the self-leveling primer to dry. When forming the self-leveling primer layer 4, it is preferable to clean the surface of the concrete floor layer 2 on which the self-leveling primer layer 4 will be formed beforehand.
[0021] The main component of the self-leveling primer may be, for example, a water-based resin emulsion. Examples of resins constituting the resin emulsion include acrylic acid ester polymers, styrene / acrylic acid ester copolymers, vinyl acetate polymers, ethylene / vinyl acetate copolymers, vinyl acetate / versatile vinyl copolymers, etc. Commercially available resins (resin emulsions) can be used. The resin in the resin emulsion may be an acrylic acid ester polymer or a styrene / acrylic acid ester copolymer. The minimum film-forming temperature (MFT) of the resin emulsion may be 0°C or higher.
[0022] The amount of self-leveling primer to be applied should be 30-120 g / m², considering the resin solid content contained in the primer, from the viewpoint of obtaining good and stable adhesive strength. 2 Or 45-90g / m 2 This is acceptable. The application can be done in one go to achieve this amount, or it can be done multiple times with time intervals in between to achieve this amount.
[0023] The drying time of the self-leveling primer can be set appropriately depending on temperature conditions, ventilation conditions, etc. For example, the drying time of the self-leveling primer may be 3 to 8 hours in summer and 5 to 12 hours in winter.
[0024] The thickness of the self-leveling material primer layer 4 may be 5-200 μm, 10-150 μm, 15-100 μm, or 20-75 μm, from the viewpoint of firmly bonding the concrete floor layer 2 and the self-leveling material layer 6.
[0025] <Second step> In this process, a predetermined self-leveling material slurry is poured onto the upper surface 4A of the self-leveling material primer layer 4, and the self-leveling material slurry is hardened to create a self-leveling material layer 6 containing the hardened self-leveling material slurry (see Figures 1(b) and 1(c)). This makes it possible to obtain a concrete floor base 10 comprising a concrete floor layer 2, a self-leveling material primer layer 4, and a self-leveling material layer 6 in that order.
[0026] The self-leveling slurry for forming the self-leveling layer 6 contains a self-leveling material and water. The self-leveling material contains a hydraulic component and resin powder.
[0027] The hydraulic component includes alumina cement. Several types of alumina cement with different mineral compositions are known and commercially available. In all cases, the main component is monocalcium aluminate (CA), and commercially available products can be used regardless of the type. The main component of alumina cement is calcium aluminate. Examples of calcium aluminate include CA, C 12 Examples include A7, C4AF, and C2AS. Alumina cement may contain only one of these calcium aluminates, or it may contain multiple types of calcium aluminates.
[0028] The hydraulic component includes Portland cement. Examples of Portland cement include ordinary Portland cement, high-early-strength Portland cement, ultra-high-early-strength Portland cement, moderate-heat Portland cement, low-heat Portland cement, and white Portland cement. Commercially available Portland cement can also be used. From the viewpoint of workability, ordinary Portland cement or high-early-strength Portland cement may be used.
[0029] The hydraulic component includes gypsum. Examples of gypsum include anhydrous gypsum, hemihydrate gypsum, and dihydrate gypsum. The gypsum functions as a component that maintains the dimensional stability of the self-leveling material layer 6.
[0030] The hydraulic component may consist of alumina cement, Portland cement, and gypsum. In this case, the content of alumina cement, Portland cement, and gypsum shall be based on the total amount of the hydraulic component (alumina cement, Portland cement, and gypsum), respectively. Alumina cement content: 10-80% by mass Portland cement content: 5-70% by mass Gypsum content: 5-45% by mass It is preferable that this be the case. Alumina cement content: 15-70% by mass Portland cement content: 10-60% by mass Gypsum content: 10-40% by mass It is more preferable that, Alumina cement content: 20-60% by mass Portland cement content: 20-50% by mass Gypsum content: 15-35% by mass It is even more preferable that this be the case.
[0031] By using hydraulic components with such a composition, it is easier to obtain a self-leveling material layer that is fast-setting, has low shrinkage or low expansion, and exhibits minimal volume change during curing.
[0032] The hydraulic component content may be 20% by mass or more, 25% by mass or more, or 30% by mass or more, and may be 60% by mass or less, 55% by mass or less, or 50% by mass or less, based on the total amount of the self-leveling material.
[0033] Examples of resin powders include powdered resins such as vinyl acetate polymer, ethylene / vinyl acetate copolymer, vinyl acetate / vinyl versatate copolymer, vinyl acetate / acrylic acid ester copolymer, acrylic acid ester / vinyl acetate / vinyl versatate copolymer, acrylic acid ester polymer, styrene / acrylic acid ester copolymer, and acrylic acid ester / methacrylic acid ester copolymer. From the viewpoint of abrasion resistance, the resin in the resin powder may contain copolymers having structural units derived from vinyl acetate.
[0034] Self-leveling materials are preferably supplied with pre-mixed components, as this allows for strict quality control of the mixing ratio of the constituent components. From the viewpoint of pre-mixing, it is preferable to use a re-emulsifiable resin powder as the resin powder.
[0035] The glass transition temperature (Tg) of the resin in the resin powder may be -20°C or higher, -10°C or higher, 0°C or higher, 5°C or higher, or 10°C or higher. The upper limit of the glass transition temperature (Tg) of the resin in the resin powder may be 40°C or lower, or 30°C or lower. In this specification, the glass transition temperature (Tg) may be measured in accordance with the provisions of JIS K 7121:2012.
[0036] The resin powder may be a powder with a residue of 3% or less on a 315 μm sieve, a powder with a residue of 3% or less on a 300 μm sieve, or a powder with a residue of 2% or less on a 300 μm sieve.
[0037] The resin powder content is 21.0 parts by mass or more and less than 40.0 parts by mass per 100 parts by mass of the hydraulic component. When the resin powder content is 21.0 parts by mass or more per 100 parts by mass of the hydraulic component, it is possible to improve the adhesion durability of the floor coating layer to the self-leveling material layer when using a water-based rigid urethane floor coating as the floor coating finish material. When the resin powder content is less than 40.0 parts by mass per 100 parts by mass of the hydraulic component, it is possible to suppress the phenomenon of the surface drying and forming a skin (or film) when forming the self-leveling material layer. By suppressing the occurrence of skin formation, it is possible to suppress the occurrence of irregularities on the surface of the self-leveling material layer, and as a result, it is possible to obtain a concrete floor structure with excellent smoothness. The resin powder content may be 22.0 parts by mass or more, and may be 39.0 parts by mass or less, 35.0 parts by mass or less, 32.0 parts by mass or less, 30.0 parts by mass or less, or 28.0 parts by mass or less, per 100 parts by mass of the hydraulic component.
[0038] The self-leveling material may further contain inorganic fillers, fine aggregates, etc.
[0039] Examples of inorganic fillers include blast furnace slag powder, fly ash, silica fume, calcium carbonate powder, and dolomite powder. The inorganic filler preferably contains blast furnace slag powder. Including blast furnace slag powder in the inorganic filler can improve the crack resistance of the self-leveling material layer.
[0040] The Blaine specific surface area of blast furnace slag fine powder, as specified in JIS A 6206:2013, is 3000 cm². 2 It may be 1 / g or more.
[0041] The inorganic filler content may be 1 to 150 parts by mass, 5 to 100 parts by mass, or 10 to 80 parts by mass per 100 parts by mass of the hydraulic component.
[0042] Examples of fine aggregates include sands such as silica sand, river sand, sea sand, mountain sand, and crushed sand; inorganic materials such as alumina cement clinker, silica powder, clay minerals, waste FCC catalyst, and limestone; and crushed resins such as crushed urethane, EVA foam, and foamed resin. Preferably, the fine aggregate is sands such as silica sand, river sand, sea sand, mountain sand, and crushed sand.
[0043] The amount of fine aggregate may be 30 to 500 parts by mass, 60 to 300 parts by mass, or 80 to 150 parts by mass per 100 parts by mass of the hydraulic component.
[0044] The self-leveling material may further contain admixtures such as water-reducing agents, thickeners, defoaming agents, setting accelerators, setting retarders, and shrinkage-reducing agents.
[0045] Examples of water-reducing agents include commercially available water-reducing agents such as melamine sulfonic acid formaldehyde condensate, casein, calcium caseinate, polycarboxylic acid-based agents, polyether-based agents, and polyether-polycarboxylic acid-based agents. Any type of water-reducing agent can be used.
[0046] The amount of water-reducing agent may be, for example, 0.01 to 2.0 parts by mass, or 0.05 to 1.0 parts by mass, per 100 parts by mass of the hydraulic component.
[0047] Examples of thickening agents include commercially available cellulose-based, protein-based, latex-based, and water-soluble polymer-based thickening agents. Any type of thickening agent can be used.
[0048] The amount of thickener may be, for example, 0.01 to 1.6 parts by mass, or 0.02 to 0.80 parts by mass, per 100 parts by mass of the hydraulic component.
[0049] Examples of defoaming agents include synthetic substances such as silicone-based, alcohol-based, polyether-based, and nonionic compounds, or mineral oils; and natural substances derived from plants. Any type of defoaming agent can be used.
[0050] The amount of defoaming agent may be, for example, 0.01 to 3.0 parts by mass, or 0.05 to 2.0 parts by mass, per 100 parts by mass of the hydraulic component.
[0051] Examples of setting accelerators include lithium salts, aluminum sulfate, and calcium chloride. Examples of lithium salts include inorganic lithium salts such as lithium carbonate, lithium chloride, lithium sulfate, lithium nitrate, and lithium hydroxide; and organic lithium salts such as lithium acetate, lithium oxalate, lithium tartrate, lithium malate, and lithium citrate.
[0052] The amount of the setting accelerator may be, for example, 0.01 to 3.0 parts by mass, or 0.02 to 1.5 parts by mass, per 100 parts by mass of the hydraulic component.
[0053] Examples of setting retarders include organic acids such as tartaric acid, citric acid, malic acid, and gluconic acid; alkali metal salts of these organic acids (sodium tartrate, sodium citrate, sodium malate, sodium gluconate, etc.); alkaline earth metal salts of these organic acids; inorganic acids such as bicarbonate and phosphoric acid; alkali metal salts of these inorganic acids (sodium bicarbonate, sodium phosphate); and alkaline earth metal salts of these inorganic acids.
[0054] The content of the setting retarder may be, for example, 0.01 to 2.0 parts by mass, or 0.05 to 1.0 parts by mass, per 100 parts by mass of the hydraulic component.
[0055] Examples of shrinkage reducing agents include commercially available shrinkage reducing agents such as polyalkylene glycols, polyethers, and higher alcohols. Any type of shrinkage reducing agent can be used.
[0056] The content of the shrinkage reducing agent may be, for example, 0.1 to 5.0 parts by mass, or 0.2 to 2.5 parts by mass, per 100 parts by mass of the hydraulic component.
[0057] A premixed powder of self-leveling material can be obtained by mixing hydraulic components, resin components, inorganic fillers, fine aggregates, admixtures, etc., in a mixer.
[0058] A self-leveling slurry for forming the self-leveling layer 6 can be obtained by mixing and kneading a premix of self-leveling powder with water. The mass ratio of water to self-leveling material (mass of water / mass of self-leveling material) may be 0.16-0.28, 0.17-0.27, 0.18-0.26, or 0.19-0.25. Mixing and kneading of the self-leveling material and water can be done, for example, using a hand mixer. The mixing and kneading time may be, for example, within 3 minutes.
[0059] Depending on the temperature and humidity conditions of the construction site, the self-leveling slurry usually begins to harden between 30 and 120 minutes after the completion of pouring (conversion). As hardening progresses, the surface hardness increases, forming a hardened self-leveling slurry, which then becomes a self-leveling layer 6 containing the hardened self-leveling slurry.
[0060] The curing time required to harden the self-leveling slurry to a walkable state can be set appropriately according to temperature conditions, ventilation conditions, etc. For example, the curing time required to harden the self-leveling slurry to a walkable state may be 1 to 3 hours in summer and 2 to 4 hours in winter.
[0061] It is preferable that the self-leveling material satisfies all of the following conditions (A) to (D) in the self-leveling material slurry containing the self-leveling material and the cured body containing the cured product thereof. By using such a self-leveling material, it becomes possible to construct the self-leveling material layer 6 more efficiently and stably.
[0062] Condition (A): The flow value measured in accordance with JASS 15M-103 is 190 mm or more, and may be 200 mm or more or 210 mm or more.
[0063] By using a self-leveling material that satisfies condition (A), a floor surface with excellent workability and smoothness can be formed.
[0064] Condition (B): The time required for the Shore hardness of the hardened surface to reach 10 or higher is 6 hours or less, but may be 4 hours or 2 hours or less.
[0065] By using a self-leveling material that meets condition (B), a floor surface with excellent rapid hardening properties can be formed. Furthermore, because the time until light foot traffic is possible is short, it is possible to move to the third process earlier.
[0066] Condition (C): The time during which the D-mode value of the moisture content measured by a concrete / mortar moisture meter (HI-520, HI-520-2: manufactured by Kett Scientific Research Institute Co., Ltd.) on the surface of the hardened material is less than 780 is 72 hours or less, but may be 48 hours or 24 hours or less.
[0067] By using a self-leveling material that satisfies Condition (C), a floor surface with excellent quick-drying properties can be formed. In addition, since the time required for the D-mode value of the moisture content measured using a concrete / mortar moisture meter (HI-520, HI-520-2: manufactured by Kett Electric Laboratory Co., Ltd.) to fall below 780 is short, the process can proceed to the third step at an early stage.
[0068] Condition (D): The compressive strength at a material age of 28 days measured in accordance with JASS 15M-103 is 30 N / mm 2 or more, and may be 35 N / mm 2 or more, or 40 N / mm 2 or more.
[0069] By using a self-leveling material that satisfies Condition (D), a concrete floor structure with excellent durability can be formed as a base for a coated floor finishing material used for traveling of heavy machinery and the like.
[0070] The self-leveling material layer 6 can be formed, for example, by the following method. First, self-leveling material slurry is placed (applied, poured) onto the upper surface 4A of the self-leveling material primer layer 4. Next, the surface of the placed self-leveling material slurry is homogenized using a trowel or a leveling rake. Thereafter, by curing the self-leveling material slurry, the self-leveling material layer 6 containing the cured product of the self-leveling material slurry can be formed. When the self-leveling material layer 6 is formed by such a method, the slurry cures while the surface remains homogenized, so that the self-leveling material layer 6 with excellent smoothness can be obtained.
[0071] The thickness of the self-leveling material layer 6 may be 1 to 100 mm, 5 to 50 mm, 7 to 40 mm, or 10 to 30 mm.
[0072] <Third Step> In this process, a floor coating material is applied to the upper surface 6A of the self-leveling material layer 6, and the floor coating material is hardened to create a floor coating material layer 8 containing the hardened floor coating material (see Figures 1(c) and 1(d)).
[0073] The floor coating layer 8 is a layer that provides the main functions such as durability, mechanical strength, and chemical resistance. The floor coating material used to form the floor coating layer 8 is a water-based rigid urethane floor coating material. A water-based rigid urethane floor coating material is a type of floor coating material mainly composed of urethane resin, which may consist of a resin part made of polyol and isocyanate, water, cement, etc., and is a urethane resin-based floor coating material that uses water as a solvent. For example, by simultaneously carrying out the urethane reaction by polyol and isocyanate and the hydration reaction by cement and water, a highly durable coating film can be obtained that combines the properties of urethane resin and mortar. Commercially available floor coating materials can be used.
[0074] The application of floor coating materials can be carried out in accordance with the application instructions of each floor coating material manufacturer, using a trowel, roller, or brush as appropriate.
[0075] The amount of floor coating material to be applied should be 2.0 to 20.0 kg / m², from the perspective of improving durability. 2 3.0~14.0 kg / m 2 4.0~8.0 kg / m 2 , or 5.0~7.0 kg / m 2 This is acceptable. The application can be done in one go to achieve this amount, or it can be done multiple times with time intervals in between to achieve this amount.
[0076] By curing the floor coating material, it can be hardened, forming a floor coating layer 8 containing the hardened material. The curing time for the floor coating material can be set appropriately according to temperature conditions, ventilation conditions, etc. The drying time (hardening time) for the floor coating material may be, for example, 24 hours or more.
[0077] The thickness of the floor coating layer 8 may be 1.0 to 10.0 mm, 1.5 to 7.0 mm, 2.0 to 4.0 mm, or 2.5 to 3.5 mm, from the viewpoint of improving durability.
[0078] The manufacturing method of the concrete floor structure 20 of this embodiment may further include a step of applying a floor coating topcoat to the upper surface of the floor coating finish layer 8 to form a floor coating topcoat layer.
[0079] The topcoat layer of the floor coating material is a layer for protecting the floor finishing material layer 8, which has properties such as weather resistance, stain resistance, slip resistance, and a matte finish, or for imparting various other functions. The main component of the topcoat for forming the topcoat layer of the floor coating material may be a resin-based topcoat. Examples of resin-based topcoats include water-based epoxy resins, water-based urethane resins, water-based methacrylic resins, water-based acrylic resins, water-based polyester resins, water-based vinyl ester resins, solvent-based epoxy resins, solvent-based urethane resins, solvent-based acrylic resins, solvent-free epoxy resins, solvent-free urethane resins, moisture-curing urethane resins, methacrylic resins, polyester resins, vinyl ester resins, and the like. One or more of these can be appropriately selected to form one or more layers of the topcoat layer of the floor coating material.
[0080] The application of the topcoat for floor coatings can be carried out in accordance with the application instructions of each floor coating manufacturer, using a trowel, roller, or brush as appropriate.
[0081] Through the above process, when a water-based rigid urethane floor coating is used as the floor coating material, a concrete floor structure 20 can be obtained that has excellent adhesion durability of the floor coating layer to the self-leveling material layer, as well as excellent smoothness.
[0082] [Concrete floor structure] The concrete floor structure of this embodiment is shown in Figure 1(d). The concrete floor structure 20 comprises a concrete floor layer 2, a self-leveling primer layer 4, a self-leveling material layer 6, and a floor coating finish layer 8 in this order. The concrete floor structure of this embodiment may be used, for example, in buildings. In particular, it can be suitably used as a concrete floor structure for non-residential buildings that require high durability, such as public facilities like hospitals and train stations (within their premises), factories, and warehouses. [Examples]
[0083] The present invention will be described in more detail below with reference to examples. However, the present invention is not limited to these examples.
[0084] [Materials used] (A) Self-leveling primer A-1: A dispersion prepared by adding water to a styrene / acrylic ester copolymer emulsion (commercial product) to adjust the solid content concentration to 15% by mass (minimum film-forming temperature: 0°C).
[0085] (B) or (b) Self-leveling material Self-leveling materials b-1 to b-3 and B-1 to B-3 were prepared by mixing the following raw materials in the proportions (parts by mass) shown in Table 1. The admixtures in Table 1 were prepared by mixing the following raw materials in the proportions (parts by mass) shown in Table 2. (1) Hydraulic component • [AC] Alumina Cement • [H] High-strength Portland cement ·[GG]Anhydrite (2) Resin powder (re-emulsified resin powder) • [2A] Vinyl acetate / acrylic acid ester copolymer (LDM2077P, Japan Coating Resin Co., Ltd., glass transition temperature: 10℃) • [2B] Ethylene / vinyl acetate copolymer (VINNPAS5010N, Wacker Chemie AG, glass transition temperature: 16°C) (3) Inorganic filler • [3A] Blast furnace slag fine powder (4) Fine aggregate ·[4A] No. 6 silica sand (5) Admixtures (5-1) Water-reducing agent • [5-1A] Polycarboxylic acid systems (5-2) Thickening agents • [5-2A] Hydroxyethylmethylcellulose • [5-2B] Polycarboxylate ethers (5-3) Antifoaming agent • [5-3A] Polyether-based • [5-3B] Nonionic (5-4) Coagulation accelerator • [5-4A] Lithium carbonate • [5-4B] Aluminum sulfate (5-5) Coagulation retarders • [5-5A] Sodium tartrate • [5-5B] Sodium Bicarbonate
[0086] [Table 1]
[0087] [Table 2]
[0088] (C) Floor coating finish C-1: Water-based rigid urethane floor coating material (commercially available, two-component type)
[0089] (Example 1) [Manufacturing of concrete floor structures] <Formation of a self-leveling primer layer> A self-leveling primer A-1 was uniformly applied to the upper surface of a concrete floor layer (concrete paving slab measuring 300mm in length, 300mm in width, and 60mm in thickness), and allowed to dry for one day to form a self-leveling primer layer.
[0090] <Preparation of self-leveling slurry> A self-leveling slurry was prepared using self-leveling material B-1. Specifically, 1.5 kg of self-leveling material B-1 was mixed with 330 g of water and kneaded for 3 minutes using a chemical stirrer (hand mixer). The preparation was carried out in a constant temperature and humidity room set at 20°C and 65% RH.
[0091] <Formation of a self-leveling layer> The self-leveling material slurry prepared above was poured to a thickness of 20 mm and cured for 7 days to form a self-leveling material layer containing the hardened self-leveling material slurry.
[0092] <Formation of the floor coating finish layer> A predetermined amount of floor coating material C-1 was applied to the upper surface of the self-leveling material layer to a thickness of 3.0 mm, forming a floor coating material layer. The application was carried out in two stages, with the second application performed 24 hours after the first application. After the second application, the structure was cured for 7 days to obtain the concrete floor structure of Example 1.
[0093] [evaluation] <Evaluation of skin-like surface development of self-leveling material slurry> The skinning of the self-leveling material slurry was evaluated by pouring the self-leveling material slurry prepared above into a 130 × 190 mm resin mold to a thickness of 10 mm in an environment of 20°C and 65% RH. After 30 minutes, the unhardened surface was cut with a cement knife, and the condition of the cut surface was observed. A score of 3 was given if no skinning was observed, a score of 2 was given if skinning was observed, the wrinkles created when the skin was cut blended into the slurry, and there were no irregularities on the surface of the self-leveling material after hardening, and a score of 1 was given if skinning was observed, the wrinkles created when the skin was cut did not blend into the slurry, and there were irregularities on the surface of the self-leveling material after hardening. A higher score indicates that the occurrence of irregularities on the surface of the self-leveling material layer can be suppressed, and therefore the smoothness of the resulting concrete floor structure is higher. The results are shown in Table 3.
[0094] <Evaluation of adhesion durability of concrete floor structures> The adhesion durability of concrete floor structures was evaluated by applying a load for 50 cycles, with each cycle consisting of 3 hours at -5°C and 1 hour at 40°C. The warping height of the floor coating layer was then measured. Warping height was defined as the height from the top surface of the self-leveling material layer to the bottom surface of the floor coating layer. A score of 3 was given for no observed warping (indicating excellent adhesion durability), 2 points for warping height less than 5 mm, and 1 point for warping height of 5 mm or more. The results are shown in Table 3.
[0095] (Example 2) Except for changing self-leveling material B-1 to self-leveling material B-2, the concrete floor structure of Example 2 was obtained in the same manner as in Example 1. The self-leveling material slurry and the concrete floor structure were evaluated in the same manner as in Example 1. The results are shown in Table 3.
[0096] (Example 3) Except for replacing self-leveling material B-1 with self-leveling material B-3, the concrete floor structure of Example 3 was obtained in the same manner as in Example 1. The self-leveling material slurry and the concrete floor structure were evaluated in the same manner as in Example 1. The results are shown in Table 3.
[0097] (Comparative Example 1) A concrete floor structure for Comparative Example 1 was obtained in the same manner as in Example 1, except that self-leveling material B-1 was replaced with self-leveling material b-1. The self-leveling material slurry and the concrete floor structure were evaluated in the same manner as in Example 1. The results are shown in Table 3.
[0098] (Comparative Example 2) A concrete floor structure for Comparative Example 2 was obtained in the same manner as in Example 1, except that self-leveling material B-1 was replaced with self-leveling material b-2. The self-leveling material slurry and the concrete floor structure were evaluated in the same manner as in Example 1. The results are shown in Table 3.
[0099] (Comparative Example 3) A concrete floor structure for Comparative Example 3 was obtained in the same manner as in Example 1, except that self-leveling material B-1 was replaced with self-leveling material b-3. The self-leveling material slurry and the concrete floor structure were evaluated in the same manner as in Example 1. The results are shown in Table 3.
[0100] [Table 3]
[0101] In Table 3, the resin powder content (in parts by mass) is the content relative to 100 parts by mass of the hydraulic component.
[0102] As shown in Table 3, the concrete floor structure of the example in which the resin powder content was within the predetermined range showed suppressed skinning of the self-leveling material slurry, suppressed the occurrence of irregularities on the surface of the self-leveling material layer, and also exhibited higher adhesion durability compared to the concrete floor structure of the comparative example in which the resin powder content was outside the predetermined range. These results confirm that the manufacturing method of the concrete floor structure of the present invention, when using a water-based rigid urethane floor coating as the floor coating finish material, can improve the adhesion durability of the floor coating layer to the self-leveling material layer, and furthermore, can obtain a concrete floor structure with excellent smoothness. [Explanation of Symbols]
[0103] 2...Concrete floor layer, 4...Self-leveling primer layer, 6...Self-leveling material layer, 8...Floor coating finish layer, 10...Concrete floor substrate, 20...Concrete floor structure.
Claims
1. A method for manufacturing a concrete floor structure comprising a concrete floor layer, a self-leveling primer layer, a self-leveling material layer, and a floor coating finish layer in this order, A step of applying a self-leveling primer layer to the upper surface of the concrete floor layer, The process involves applying a self-leveling material slurry containing a self-leveling material with a hydraulic component and resin powder, and water, to the upper surface of the self-leveling material primer layer, and curing the self-leveling material slurry to provide a self-leveling material layer containing the cured product of the self-leveling material slurry. The process involves applying a floor finishing material to the upper surface of the self-leveling material layer and curing the floor finishing material to provide a floor finishing material layer containing the cured product of the floor finishing material, Equipped with, The hydraulic component includes alumina cement, Portland cement, and gypsum. The content of the resin powder is 21.0 parts by mass or more and less than 40.0 parts by mass per 100 parts by mass of the hydraulic component. The aforementioned floor coating material is a water-based rigid urethane floor coating material. A method for manufacturing concrete floor structures.
2. The resin in the aforementioned resin powder includes a copolymer having structural units derived from vinyl acetate. A method for manufacturing a concrete floor structure according to claim 1.
3. Concrete floor layer, Self-leveling primer layer, Self-leveling material layer, The floor coating finish layer, They are provided in this order, The self-leveling material layer comprises a self-leveling material containing a hydraulic component and resin powder, and a cured self-leveling material slurry containing water. The hydraulic component includes alumina cement, Portland cement, and gypsum. The content of the resin powder is 21.0 parts by mass or more and less than 40.0 parts by mass per 100 parts by mass of the hydraulic component. The floor coating layer contains hardened material of the floor coating, The aforementioned floor coating material is a water-based rigid urethane floor coating material. Concrete floor structure.
Citation Information
Patent Citations
Concrete floor structure and its construction method
JP2009257063A